PENGARUH DURASI TETESAN PADA BUDIDAYA TOMAT DENGAN IRIGASI TETES IN-LINE DRIP - Sumardi, Aurelius; Lano, Marten Luter; Makaborang, Marthen (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2025)
Research on the duration of drips in in-line drip irrigation for tomato cultivation in semi-arid areas was conducted at the FTP-UKAW Kupang Field Laboratory from April to August 2025. This experimental study was designed as a completely randomized design (CRD) with 4 treatments and 5 replicates. The treatments tested were P1 = 40-minute drip duration, P2 = 50-minute drip duration, P3 = 60-minute drip duration, and P4 = 70-minute drip duration. Observations on the research variables, including plant height, number of leaves, total number of fruits, and total weight of tomato fruit, were analyzed using analysis of variance (ANOVA) to determine the effect of treatment, and Duncan's multiple range test was used to identify the best treatment. The results showed that the duration of irrigation water supply with in-line drip had a significant effect on plant height, number of leaves, total number of fruits, and total weight of tomato fruit. The study found that longer drip durations further improved tomato growth performance and fruit production. The best irrigation water supply with in-line drip was provided by the 70-minute drip duration treatment (P4), which yielded the highest values for each test variable, namely an average height of 104.60 cm, an average number of leaves of 116 strands, an average total number of fruits of 55.4 fruits, and an average total weight of 3,490 grams of tomatoes.